Political Public Relations: Public Presentation of Real Works or Tool to Blame Opponents for Inadequate Activities? - Matkevičienė, Renata (Parliamentary Studies, 2015)
In the public sphere, especially before elections, discussions about the possibilities of political communication or techniques of public relations could show that politicians are familiar with the means of political public relations and they tend to see those means applied by their political opponents via presentation of problems and their solutions, suggested procedures to consolidate political partners and electorate for some decisions, etc. Politics is a field in which modern communications and public relations were invented, and in this field public relations could help present ideas, organize discussions on topics that are important for groups of society. In politics, public relations is essential not only during political election campaigns when voters are introduced to policies or political parties, politicians, but also on a daily basis , because only because of communicating with each other and with the public and relevant stakeholders groups politicians and political institutions can ensure the enforcement of the policy: formation of governments, coalitions, to address public interest issues and trade-offs in negotiating party or parties with different representatives, businessmen and politicians of other countries . Political public relations covers a wide range of communication means, so it sometimes becomes annoying when politicians in the public space treat public relations only as a political desire to be visible and popular. The aim of this article is to present definition and discussion about political public relations, their characteristics, principles, in order to refute the prevailing media myths about public relations activities. This article analyzes political public relations activities, processes and means that are used for political public relations. In the article the main fields of activities of public relations such as media relations, image management, and internal political communication are presented. In the conclusions the myths related with political public relations are discussed: usage of term public relations to strengthen populist aspects of political opponents’ activities, importance of media relations and image formation, visibility creation and political spectacle as the main activities of political public relations.